Assessment of Patients Knowledge Undergoing Chemotherapy toward Self Care after Gastrectomy at Oncology Unit of Al-Haboby Teaching Hospital in AL-Naseria City - Hussein A. Jabbar; Suad J. Muhamad (Kufa Journal for Nursing Sciences)
Background: Knowledge of self-care is an important index for evaluating the outcomes of treatment and the long-term survival of patients with cancer.